Fat oxidation, fitness and skeletal muscle expression of oxidative/lipid metabolism genes in South Asians: implications for insulin resistance? - Lesley M L Hall; Colin N Moran; Gillian R Milne; John Wilson; Niall G MacFarlane; Nita G Forouhi; Narayanan Hariharan; Ian P Salt; Naveed Sattar; Jason M R Gill (PLoS ONE, 2010)
South Asians are more insulin resistant than Europeans, which cannot be fully explained by differences in adiposity. We investigated whether differences in oxidative capacity and capacity for fatty acid utilisation in South Asians might contribute, using a range of whole-body and skeletal muscle measures.Twenty men of South Asian ethnic origin and 20 age and BMI-matched men of white European descent underwent exercise and metabolic testing and provided a muscle biopsy to determine expression of oxidative and lipid metabolism genes and of insulin signalling proteins. In analyses adjusted for age, BMI, fat mass and physical activity, South Asians, compared to Europeans, exhibited; reduced insulin sensitivity by 26% (p = 0.010); lower VO2max (40.6±6.6 vs 52.4±5.7 ml x kg(-1) x min(-1), p = 0.001); and reduced fat oxidation during submaximal exercise at the same relative (3.77±2.02 vs 6.55±2.60 mg x kg(-1) x min(-1) at 55% VO2max, p = 0.013), and absolute (3.46±2.20 vs 6.00±1.93 mg x kg(-1) x min(-1) at 25 ml O(2) x kg(-1) x min(-1), p = 0.021), exercise intensities. South Asians exhibited significantly higher skeletal muscle gene expression of CPT1A and FASN and significantly lower skeletal muscle protein expression of PI3K and PKB Ser473 phosphorylation. Fat oxidation during submaximal exercise and VO2max both correlated significantly with insulin sensitivity index and PKB Ser473 phosphorylation, with VO2max or fat oxidation during exercise explaining 10-13% of the variance in insulin sensitivity index, independent of age, body composition and physical activity.These data indicate that reduced oxidative capacity and capacity for fatty acid utilisation at the whole body level are key features of the insulin resistant phenotype observed in South Asians, but that this is not the consequence of reduced skeletal muscle expression of oxidative and lipid metabolism genes.